VD_FINDINFO Jug / 2017 / 169 vom 27. Juni 2008 - VD Tribunal cantonal (2008)
DEMANDE ADRESSÉE À L'AUTORITÉ, RÉVISIONDÉCISION, RÉCUSATION, TÉMOIN, REJET DE LA DEMANDE | 410 CPP (CH), 411 CPP (CH), 451 CPP (CH)